2015
DOI: 10.1111/gcbb.12299
|View full text |Cite
|
Sign up to set email alerts
|

Global change synergies and trade‐offs between renewable energy and biodiversity

Abstract: Reliance on fossil fuels is causing unprecedented climate change and is accelerating environmental degradation and global biodiversity loss. Together, climate change and biodiversity loss, if not averted urgently, may inflict severe damage on ecosystem processes, functions and services that support the welfare of modern societies. Increasing renewable energy deployment and expanding the current protected area network represent key solutions to these challenges, but conflicts may arise over the use of limited l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 45 publications
1
71
0
4
Order By: Relevance
“…This map approximates installed and planned national wind energy capacity (REN21 ; Santangeli et al. ) and has been used to evaluate impacts of wind energy expansion on biodiversity (Santangeli et al , , ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This map approximates installed and planned national wind energy capacity (REN21 ; Santangeli et al. ) and has been used to evaluate impacts of wind energy expansion on biodiversity (Santangeli et al , , ).…”
Section: Methodsmentioning
confidence: 99%
“…We used Pogson et al's (2013) map of wind-power potential as a proxy for exposure to collision with wind turbines, a major threat to vultures (Pearce-Higgins & Green 2014; Ogada et al 2016b;Botha et al 2017). This map approximates installed and planned national wind energy capacity (REN21 2017; Santangeli et al 2018) and has been used to evaluate impacts of wind energy expansion on biodiversity (Santangeli et al 2016b(Santangeli et al , 2016c(Santangeli et al , 2018.…”
Section: Wind Collision Riskmentioning
confidence: 99%
“…This has led to substantial concerns that land requirements for bioenergy crops would be competing with conservation areas directly or by leakage. Santangeli et al (2016) found around half of today's global bioenergy production potential to be located either in already protected areas or in land that has highest priority for protection, indicating a high risk for biodiversity in the absence of strong regulatory conservation efforts.…”
Section: Potential Impacts On Biodiversitymentioning
confidence: 99%
“…This may result in impacts (e.g. expansion of anthropogenic land uses) that may spill over areas of key importance for biodiversity, such as primary forests in tropical areas (Fargione et al ., ; Wich et al ., ; Santangeli et al ., ). Many such areas have previously been identified as biodiversity hotspots (Myers et al ., ), key sites with species in imminent danger of becoming extinct (Alliance for Zero Extinction sites; http://www.zeroextinction.org) and sites with natural habitats of irreplaceable biodiversity value (Gibson et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…We calculated land‐based solar photovoltaic, wind (hereafter solar and wind) and bioenergy unrestricted potential (see Pogson et al ., ; for more information) within the 70% fraction of the landscape with least importance for biodiversity conservation in each country (data from Pouzols et al ., ). We set the 70% threshold for this study because it implies that 30% of each country's land would be excluded from development, allowing for the cost‐efficient achievement of global biodiversity conservation targets (Pouzols et al ., ; Butchart et al ., ) and a measurable expansion of RE development (Santangeli et al ., ). Calculations were made in arcgis 10.1 (ESRI, Redlands, CA, USA) using the zonal statistics tool and accounting for the change in cell size by latitude.…”
Section: Methodsmentioning
confidence: 97%